Programme theory development and formative evaluation of a provincial knowledge translation unit - Denise Thomson; Stephanie Brooks; Megan Nuspl; Lisa Hartling (BMC, 2019)
Abstract Background Research shows a significant gap between healthcare research and evidence-based healthcare policy and practice. Knowledge translation (KT) has an important role in addressing this gap by bolstering evidence-informed healthcare. Canada's Strategy for Patient-Oriented Research (SPOR) is a nationally mandated and supported initiative developed to respond to the gap between research and practice. One aspect of SPOR is the provincial/territorial SUpport for People and Patient-Oriented Research and Trials (SUPPORT) Units, intended to assist local health researchers and systems to reach the goal of improving the quality and quantity of patient-oriented research in Canada. This article presents the programme theory development and a formative evaluation of the KT Platform in Alberta's SPOR SUPPORT Unit. Methods We used a mixed-methods approach to develop the KT Platform's programme theory and subsequently conducted the formative evaluation. An extensive needs assessment, comprised of 59 qualitative interviews with researchers and health systems employees in Canada with an interest in KT, served as the basis for our programme theory design. Three years after launching the KT Platform, we hired an evaluation consultant to conduct a formative evaluation of the Platform's programme theory and operations. The evaluation was performed by conducting nine interviews with KT Platform service users (n = 6) and KT experts acting in advisory capacities to the KT Platform (n = 3). Results The KT Platform developed a '4C Model' as a summary of the Platform's programme theory. This model is designed to meet local needs for capacity-building, a community of practice, consultation services, and contributions to KT science. This suite of services was found to help the local health system implement health evidence with measurable positive health outcomes. However, the community remains hesitant about their capacity as individuals to design and perform important KT activities independently. Conclusions With the mandate and support provided by SPOR, the KT Platform was able to design a strong programme theory based on evidence from an extensive needs assessment of the local community. The resulting 4C Model has provided a framework for KT work to assist in improving local health outcomes and can be considered by others designing KT programmes as a useful model to follow. Ongoing monitoring and assessment are required to continue to identify and respond to local needs.